Mini smart car - Ismail, Nuurdianty (2006)
The projects on an autonomous Mini Smart Car (MSC) were implementing and design to become a fully autonomous robot. The robot was integrated with microcontroller to producing an embedded system that integrates hardware and software in this design. The essential components for a Mini Smart Car (MSC) is include an environment sensors, navigational intelligence and actuators (wheel). The Mini Smart Car was developed with incorporated with an infra red sensors input devices as environment sensors and two dc motors (which control the wheel) as an actuator.